Better innovation, better future: working together for innovating Asia. Issue 1 (2nd January 2017) - Lee, Kong-rae; Chen, Jin; Li, Jizhen; Kim, Jang Hyun
Abstract : This special issue of Asian Journal of Technology Innovation aims at contributing to academic collaborations and exchanges of scholars in Asia including CICALICS and ASIALICS members. By introducing 12 research articles, this special issue discloses how firms, individuals, and nations are striving to catch up with other advanced entities, enlarge their excellence over competitors, and cooperate among university-government-industry (triple helix) sectors. Strength of research in innovation studies lie in theoretical accounts of innovation, lively cases from the innovation's real world, and systematic approaches to innovations.